Regression equation for estimation of total humeral length using measurements of its proximal segments among Indian population - B M Lakshmi Kantha; N S Naveen; Roopa Kulkarni; V Veena (Wolters Kluwer Medknow Publications, 2016)
Background: The aim of the present study was to calculate regression equation for the estimation of total length of the humerus using the measurements of its proximal fragments in Indian population. This equation is essential for forensic investigators for estimating the humeral length and also height of individual using humeral length when fragments of humerus are available in forensic investigation. Materials and Methods: In the present study 150 (75 left and 75 right) adult, fully ossified, dry and processed humerii were taken to analyze the morphometric details of the humeral segments which were measured using osteometric board and scale. The distance between three different segments namely, from most proximal point in the head to most distal point of the circumference of the head (segment- 1), from most distal point of the circumference of the head to the convergence of two areas of muscle attachment (segment-2), the convergence of two areas of muscle attachment to the deltoid tuberosity (segment- 3) and maximum length of humerus were measured to the nearest millimeter. The association between the humeral segments and maximum humeral length was calculated using Pearson's correlation coefficient (r) and later linear regression was applied considering left and right humerii separately. Results: The regression equation of humerus segments -1,2 and 3 were MHL - Maximum humeral length = 175.05 + [3.58(H1)], MHL = 185.80 + [2.18(H2)], MHL = 161.44 + [2.18(H3>] on left and MHL = 171.91 + [3.74(H1)], MHL = 195.54 + [1.95(H2)], MHL = 229.03 + [1.24(H3)] on right side of humerus respectively. This regression equation of Mean total length of humerus using its proximal fragmentary bone length will help for the stature estimation of individual. Conclusion: This study helps in forensic, anatomic and archeological fields in order to identify human remains of unknown persons.